2021
DOI: 10.3991/ijoe.v17i08.23359
|View full text |Cite
|
Sign up to set email alerts
|

Practical Work of Digital System Course Based on Virtual Laboratory

Abstract: In this paper, a virtual laboratory is used for digital systems practice courses which are carried out online. The research step begins with designing a virtual laboratory portal with Moodle E-Learning software to provide practice management services. The trial was carried out by running an online collaborative practice by applying the Breadboard simulator and the TeamViewer application. The research subjects were 20 students of the Informatics Engineering study program. The data collection instrument used a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Their research was carried out with 20 engineering students as subjects. The results showed that the online laboratory platform had a positive perception from the students in terms of the educational aspect, the learning model, and means of operation, increasing the students' motivation as well [9].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Their research was carried out with 20 engineering students as subjects. The results showed that the online laboratory platform had a positive perception from the students in terms of the educational aspect, the learning model, and means of operation, increasing the students' motivation as well [9].…”
Section: Related Workmentioning
confidence: 99%
“…Previous research in the field of remote laboratories proved that these platforms could improve students' understanding of the lessons, sometimes being even more efficient than real laboratories due to wide accessibility and flexibility, as they can be accessed anytime, anywhere, and from any connected device. Furthermore, they are less expensive and can be used to teach a high number of students [9].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For cognitive measurement, the result shows that all questions were above 3.68, which means the student had a high perception regarding learning materials, including guidelines and manuals, where most of the information provided by the lecturer was adequate to do the virtual and remote experiments. TeamViewer was embedded in the remote laboratory model, which comprises easy-to-learn online learning instructions, simulator usage instructions, and digital practise instructions (Mulya et al, 2021). Having a high mean value score of 4.15, the subject or exercise was simple to learn as the student was able to complete the task given on time with minimal mistakes, as measured through question number 6.…”
Section: Part C: Online Laboratory Practices For Che249-separation Pr...mentioning
confidence: 99%
“…On-line learning process is not just to transfer learning modules to students, but lecturers must be able to guide students in an unlimited time, whenever students need an explanation of the material provided, which is accompanied by showing directly and wherever the lecturer is [2]. The right solution to overcome the problem of on-line lectures is to use TeamViewer via smart phone or laptop media, for remote learning specifically on PLC (Program Logic Control) courses related to programming and its applications [3].…”
Section: Introductionmentioning
confidence: 99%